1995
DOI: 10.1111/j.1748-1716.1995.tb09841.x
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone regulation of myosin heavy chain isoform composition in young and old rats, with special reference to IIX myosin

Abstract: The effects of 4 weeks of thyroid hormone (3,5,3'-triiodothyronine, T3) treatment on the myosin heavy chain (MHC) composition were compared in the slow-twitch soleus and the fast-twitch extensor digitorum longus (EDL) muscles from young (3-6 months) and old (20-24 months) male albino rats. Four MHC isoforms were separated on silver-stained 6% sodium dodecyl sulphate polyacrylamide gel electrophoresis. According to immunoblotting experiments with specific MHC monoclonal antibodies, the four MHCs corresponded to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 38 publications
3
40
1
2
Order By: Relevance
“…Rat skeletal muscles undergo a type 2B to 2X switching in aging fast muscles and a type 2A to type 1 switching in slow soleus (462)(463)(464). The histochemical fiber type profile does not appear to change with age in human skeletal muscle; however, the relative proportion of fast MyHCs is reduced in elderly subjects (423,733) due to greater atrophy of type 2 fibers (478).…”
Section: Muscle Fiber Types During Postnatal Development and Agingmentioning
confidence: 99%
“…Rat skeletal muscles undergo a type 2B to 2X switching in aging fast muscles and a type 2A to type 1 switching in slow soleus (462)(463)(464). The histochemical fiber type profile does not appear to change with age in human skeletal muscle; however, the relative proportion of fast MyHCs is reduced in elderly subjects (423,733) due to greater atrophy of type 2 fibers (478).…”
Section: Muscle Fiber Types During Postnatal Development and Agingmentioning
confidence: 99%
“…The total acrylamide and bis concentrations were 4% (wt/vol) in the stacking gel and 6% in the running gel, and the gel matrix included 30% glycerol (26). The ammonium persulfate concentrations were 0.4% and 0.029% in the stacking and separation gels, respectively, and the gel solutions were degassed (Ͻ100 mTorr) for 15 min at 18°C.…”
Section: Determination Of Myhc Isoform Composition the Myhc Compositmentioning
confidence: 99%
“…Immunoblotting experiments had been conducted previously in this laboratory to determine the migration order of the four MyHC isoforms separated by the type of gels used in this study. The migration order from slowest to fastest migrating MyHC isoform is as follows: IIa-IIx-IIb-I (26).…”
Section: Determination Of Myhc Isoform Composition the Myhc Compositmentioning
confidence: 99%
“…It has been shown that in rats full differentiation of skeletal muscle phenotype is only achieved with appropriate thyroid hormone levels (Vadaszova et al, 2004). Moreover in rats, T3 treatment significantly changes the muscle contractile properties and myosin heavy chain (MHC) isoform expression in both fast and slow muscle types (Adams et al, 1999;Larsson et al, 1994;Larsson et al, 1995;Soukup and Jirmanova, 2000). In both thyroidectomised and thioureatreated chick embryos prolonged expression of slow MHC and myosin light chains (MLC) and inhibition of neonatal fast MHC isoforms occurs in the fast posterior latissimus dorsi muscle, whereas in the slow anterior latissimus dorsi muscle slow muscle differentiation is delayed and expression of embryonic fast MHC isoforms persist and there is induction of fast MLCs (Gardahaut et al, 1992).…”
Section: Introductionmentioning
confidence: 99%